Penggunaan KIT IPA Dalam Meningkatkan Hasil Belajar IPA Siswa Kelas VI SD Negeri 6 Mataram - Endang P Handayani; Syahrial Ayub (Department of Physics Education, Universitas Mataram, 2018)
This class action research aims to enhance the learning outcomes of the 6th graders of SD Negeri 6 Mataram in their science lesson by corporating Science KIT in teaching and learning activities inside the classroom. The research was conducted in 2 cycles, each of which included 4 different steps, namely, Planning, Action, Observation, and Reflection. After the research, it is shown that the average learning outcomes and classical completeness for the first cycle are 84,7 and 84%, while the average learning outcomes and classical completeness for the second cycle are 88,4 and 94% respectively. This thus shows an improvement in the studentsÃ¢â¬â¢ learning outcomes, especially related to electrical and thermal energy. This conclusion is drawn after looking at the fact that 94% of the students score more than 75 in the test. This result is only obtained after the science KIT has already been applied in Science Lesson inside the classroom.